Copper(II)-salt-promoted oxidative ring-opening reactions of bicyclic cyclopropanol derivatives via radical pathways - Hasegawa, Eietsu; Tateyama, Minami; Nagumo, Ryosuke; Tayama, Eiji; Iwamoto, Hajime (Beilstein Journal of Organic Chemistry, 2013)
Copper(II)-salt-promoted oxidative ring-opening reactions of bicyclic cyclopropanol derivatives were investigated. The regioselectivities of these processes were found to be influenced by the structure of cyclopropanols as well as the counter anion of the copper(II) salts. A mechanism involving rearrangement reactions of radical intermediates and their competitive trapping by copper ions is proposed.
Keywords: copper(II) salt; cyclopropanol; electron transfer; free radical; radical ion probe